2011
DOI: 10.1378/chest.10-2644
|View full text |Cite
|
Sign up to set email alerts
|

Increased Adverse Events After Percutaneous Coronary Intervention in Patients With COPD

Abstract: COPDOriginal Research tion (PCI) for revascularization. Although patients with COPD currently make up almost 10% of patients undergoing PCI, 7 limited data reveal an increased risk of mortality. [7][8] Potential factors associated with this A mong the 10 most common causes of death in the United States, COPD is the only one that is increasing in frequency. 1 Independent of smoking status, patients with COPD are at increased risk for cardiovascular disease. 2 Additionally, the presence of coronary artery diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 24 publications
3
39
0
4
Order By: Relevance
“…Despite adjusting for multiple risk factors that may potentially affect clinical outcomes, COPD still remained an independent predictor of long-term cardiovascular events. Our results also showed that the patients with COPD were older and had an increased prevalence of cardiovascular risk factors, which were consistent with previous studies [1416]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite adjusting for multiple risk factors that may potentially affect clinical outcomes, COPD still remained an independent predictor of long-term cardiovascular events. Our results also showed that the patients with COPD were older and had an increased prevalence of cardiovascular risk factors, which were consistent with previous studies [1416]. …”
Section: Discussionsupporting
confidence: 93%
“…The impact of COPD on long-term mortality has been previously investigated. However, most of these studies focused on mortality, but other outcomes such as HF, revascularization, and stroke were not more studied [14, 15]. The present study involved 2362 patients who underwent PCI with diagnosis of COPD confirmed by review of medical records.…”
Section: Discussionmentioning
confidence: 99%
“…15 Studies utilizing invasive assessments have mostly consisted of retrospective analysis of angiographic data in patients undergoing coronary angiography based on clinical suspicion of disease. 13,16,17 …”
mentioning
confidence: 99%
“…Further articles were deselected since they were either case studies (2), letter to editors (1), they did not report the relevant endpoints (3), they were duplicates (8) or they were associated with the same trial or cohort (2). Finally, 10 studies [3, 4, 815] were selected for this analysis.
Fig. 1Flow diagram representing the study selection
…”
Section: Resultsmentioning
confidence: 99%